USING SMALL GROUP DISCUSSION TO IMPROVE STUDENTS’ SPEAKING ACHIEVEMENT AT SMK SORE PANGKALPINANG - SINTA S (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2020)
Abstract The title of this study is “Using Small Group Discussion to improve Students’ Speaking Achievement at SMK SORE Pangkalpinang.”.The problems of this study :“Is small group Discussion effectively used in improving students’ speaking achievement at SMK Sore Pangkalpinang?” The method of research used in this study was the experimental research. The type of experimental method used was quasi-experimental. The result of the test was analyzed by using SPSS Program. Based on the result of the data analysis, From the scores that were found, the result of statistical analysis between experimental and control group (t-obtained) should be higher than t-table (0.05) for two tailed. Furthermore the result of the students’ score in control and experimental group (value of t-obtained) was 7.541. Since the value of t-obtained was higher than t-table, so that the null hypothesis was rejected and alternative hypothesis was accepted. It can be stated that improving students’ speaking achievement using small group discussion method is more effective than conventional way to students’ at SMK SORE PANGKALPINANG. Keywords: improving, speaking, small group discussion